Biosorption of Lead and Chromium Ions by Using Penicillium digitatum (Pers.) Sacc. from Industrial Water - Hussain, Sajida Frhan; Khazaal, Duaa Sameer; Hatif, Zainab Hani (Iraqi Journal of Science, 2020)
Some microorganisms, including fungi, are characterized by their removal efficiency and reducing the concentrations of heavy metals such as Pb and Cr from industrial water. The present study aims to estimate the efficiency of Penicillium digitatum (Pers.) Sacc. as a low-cost biosorbent in reducing Pb and Cr from industrial water with optimum biosorption conditions (acidity of 1.5 , 4, and 5; temperature of 30 Â°C). The Fourier transform infrared spectroscopy (FTIR) analysis was also used for determining the roles of the functional groups in this biosorbent. The results indicated that the highest P. digitatum efficiency values for reducing the levels of Pb and Cr were 84% and 70% , respectively, at pH of 5 after 24 h. However, this efficiency was decreased from 81% to76% at pH values of 4 and 1.5, respectively, for Pb. The removal efficiency for Cr was 56% at pH of 4 after 1h. at 30 Â°C. Also, the FTIR spectra illustrated -CH, -C-N, N-H, and =CO peaks of functional groups that may change as a result of their involvement in the adsorption process of lead and chromium.